Non-invasive prenatal diagnostics - Lo, Y. M. Dennis (Henry Stewart Talks, 2012)
Overview of plasma nucleic acids, Discovery and basic biology of circulating fetal DNA, T21 detection from maternal plasma, T13/18 detection from maternal plasma, Fetal genome scanning, Targeted sequencing from maternal plasma, Size analysis of plasma DNA